Community-Based Approach to Enhancing Religious Moderation and Social Compassion in Rural Areas - Wajdi, Muh Barid Nizarudin; Wasehudin, Wasehudin; Fajarianto, Otto; Halim, Paisal; Mufidah, Luluk Indarinul (STAI Miftahul ULa Nganjuk, 2024)
This study investigates the role of community-based interventions in promoting religious moderation and fostering social compassion in Sidoharjo Village, particularly during the COVID-19 pandemic. The intervention utilized a Participatory Action Research (PAR) approach, engaging community members in the co-design and implementation of training sessions aimed at improving religious understanding and nurturing empathy. Through a series of workshops, focus group discussions, and interactive dialogues, participants were exposed to the principles of religious moderation and compassion, while also addressing local socio-cultural challenges. The results indicate positive engagement and a shift towards greater social responsibility within the community. However, the study also identifies the need for more robust quantitative data and clearer evaluation metrics to assess the long-term impact of such interventions. This research contributes to the growing body of knowledge on community-driven development and the role of religious moderation in fostering social harmony in rural communities.